2020
DOI: 10.1055/s-0040-1702262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internship Program on Self-Reported Clinical Competence among BSc Nursing Students in Selected Nursing Colleges at Mangaluru

Abstract: IntroductionNursing is a profession within the health care sector focused on the care of individuals, families, and communities, and they are the backbone of the health care team. In the early period, competency includes the assessment of personal qualities of a nurse such as values, skills, judgment, and attitude. Nursing students should be given adequate training during the study period to become clinically competent nurses and must be ready to compete with the dynamic world. Objective This study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…In the present study, working in different shifts and wards during the internship program led to exposure to various nursing procedures and acquiring skills. Kannappan et al’s study (2020) found that the internship program could help nursing students improve their skills and clinical competence [ 9 ]. In this regard, in the study by Jokhio et al, the internship program was reported to be essential for achieving professional growth and acquiring skills [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, working in different shifts and wards during the internship program led to exposure to various nursing procedures and acquiring skills. Kannappan et al’s study (2020) found that the internship program could help nursing students improve their skills and clinical competence [ 9 ]. In this regard, in the study by Jokhio et al, the internship program was reported to be essential for achieving professional growth and acquiring skills [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Internship programs provide a context in which students can put what they have learned into practice [ 7 ]. The internship program began in the United States in 1900 [ 8 ] and provided the necessary platform in nursing schools to transition from a nursing student to a new graduate [ 9 ]. This educational model is held for novice nurses in some countries and final-year nursing students in others [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there was a highly statistically significant difference between nursing interns' knowledge related to clinical and management skills required for professional nursing practice pre and post implementation of nursing interns' orientation program to develop their knowledge about professional nursing practice(p<0.0001). (10) identifies that high percent (67%) of nursing interns had unsatisfactory knowledge level related to international patient safety goals, while the majority (98.3%) had satisfactory knowledge level post program. Additionally, there was a highly statistically significant difference between nursing interns' knowledge related to EJNHS Vol.…”
Section: Administrative Design and Ethical Considerationsmentioning
confidence: 99%